Transformasi Standar Nasional dan Akreditasi Pendidikan Tinggi - Ayu Miranda Limbong; Masduki Asbari (AGUSPATI RESEARCH INSTITUTA, 2024)
- The aim of this study is to realize the vision of an advanced Indonesia that is sovereign, independent and has personality through the creation of Pancasila students. The Ministry of Education, Culture, research and technology continues to advance in presenting various breakthroughs. Freedom to learn. Freedom to learn, which is promoted by the Ministry of Education and Culture, Research and Technology, also has the aim of achieving quality education for all Indonesian people. In this report, this study uses a descriptive qualitative method by taking notes because the data source was obtained by listening to the oral narrative from the Ministry of Education and Culture's YouTube channel entitled